PENGARUH CAPITAL REQUIREMENT, LIQUIDITY RATIO, DAN LENDING STRUCTURE TERHADAP RISIKO KREDIT PERBANKAN INDONESIA - FATIMAH, . (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This study aimed to analyze the effect of capital requirement, liquidity ratio, and lending structure on Indonesia’s banking credit risk. The credit risk is measured by using Risk Adjusted Return on Capital and Loan/ Total Assets. This study used secondary data with 17 samples from Indonesia’s banking companies that are listed on the Indonesia’s Stock Exchange during the period of 2009 – 2011 and have met certain criteria. The result showed that the variables affect credit risk. Capital had similar result with researches in various countries, which indicates that capital is an important pillar in the face of Banking Risk. Lower liquidity will reduce credit risk, while that level of credit’s concentration which means the bank will determine the depth of understanding of industry’s condition also have a positive influence on credit risk.